RENCANA ANGGARAN BIAYA (RAB) UNTUK PEMBANGUNAN PASAR DENGAN FASILITAS RAMAH LINGKUNGAN DI KELURAHAN TALANG PUTRI - Akbari, Ilham; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This research aims to develop a comprehensive Budget Plan (RAB) for the construction of a market with environmentally friendly facilities in Talang Putri Village. The research employs a quantitative descriptive method with a case study approach, utilizing primary data through field surveys, interviews, and direct observations, as well as secondary data from planning documents and related regulations. The research results produced a market design that implements Green Architecture concepts with dry and wet zone divisions, equipped with environmentally friendly utility systems such as water management, integrated waste treatment, and renewable energy utilization. The budget plan was prepared considering the efficient use of local materials and cost-effective construction technology. This research provides long-term development recommendations including environmental management training, supporting facility improvements, and community involvement in market management to create a sustainable traditional market that supports the improvement of the surrounding community's quality of life.Keywords: Budget plan, traditional market, green architecture, environmentally friendly, sustainable development